Outcome of Hemispherectomy for Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The clinical course and outcomes of 33 children with refractory epilepsy and hemiplegia are evaluated following hemispherectomy at Great Ormond Street Hospital, London, between 1991 and 1997, with particular reference to the underlying pathology, freedom from seizures, change in hemiplegia, cognitive function, and behavior.